Editorial: Advances in the application of technology for monitoring horse welfare and health - Dalla Costa, Emanuela; Bovo, Marco (Frontiers in Veterinary Science, 2025)
Graphical AbstractFlowchart illustrating interdisciplinary collaboration in animal research. A horse symbolizes the focus, with pathways connecting physiology, behavior, and environment to decision-making and regulatory indications. Data analysis, system understanding, and data interpretation lead to feedback and warning. Visual elements include sun, clouds, a light bulb, gears, and a graph.